PERAN ELITE PEREMPUAN NU JAWA TIMUR DALAM KONTESTASI CAPRES-CAWAPRES 2024 - Wasid, Wasid; Rochimah, Rochimah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
This research explores the role of the NU East Java women's elite in the 2024 Presidential and Vice Presidential Contests. NU female elites, both structurally from Fatayat NU and Muslimat NU or from cultural in this case are caregivers of Islamic boarding schools, known as Bunyai and Ning, have a unique authority in choosing and determining support for the 2024 Presidential and Vice Presidential pair. This research is part of qualitative research. Therefore, the author uses role theory, as well as a webarian analysis related to the motives behind the social actions of the NU women's elite. The results of this study stated that NU women's elites, both structural and cultural, have different choices in responding to the 2024 Presidential and Vice Presidential contests, considering that their support motives are also different. The role of NU women's elites has similarities in winning their respective elections. However, the model is different between Bunyai and Ning and NU women who are active in organizations, both Fatayat NU and Muslimat NU. Of course, the maximum role and firmness of the political stance of the NU Muslimat did have a big impact on the victory of the Prabowo Subianto and Gibran Rakabuming Raka pair, although this attitude is related to the political pragmatism of the NU Muslimat Chairman to contest in the 2024 Regional Elections. Keywords : Role, Female Elite, NU, East Java